Multi-Decadal Glacier Area and Mass Balance Change in the Southern Peruvian Andes - Taylor, Liam S.; Quincey, Duncan J.; Smith, Mark W.; Potter, Emily R.; Castro, Joshua; Fyffe, Catriona L. (Frontiers in Earth Science, 2022)
Around 70% of the world’s tropical glaciers are located in Peru, and they are melting rapidly in response to climate change. The glaciers of the data-sparse Southern Peruvian Andes, comprising the Cordilleras Vilcanota, Vilcabamba, and Urubamba, are a primary water source for thousands of people living in the rural foothills, and support people throughout the wider Cusco region. Here, we calculate geodetic mass balance for the Cordillera Vilcanota (-0.48 ± 0.07 m w.e. yr-1) using the ASTER satellite archive and derive a total loss of 3.18 ± 0.44 Gt ice between 2000 and 2020. Glacierised area has shrunk rapidly since the 1970s (losses of 54%, 56%, and 64% for the Cordilleras Vilcanota, Vilcabamba, and Urubamba respectively) as a consequence of changing climatic patterns, with low-lying glaciers receding the most across all regions. We calculate a rise in the median elevation of glaciers ranging from 15.9 m per decade over the Quelccaya ice cap in the Cordillera Vilcanota, to 32.8 m per decade in the Cordillera Vilcabamba, over the period 1975 to 2020. This change implies an increased hazard potential as the mountain regions become destabilised, and will lead to increasing pressure on fresh water supply as meltwater streamflow decreases and river discharge becomes increasingly, and irreversibly, variable.